The Effect of Free Cash Flow, Leverage, Profitability, Liquidity, and Growth Opportunities on Dividend Policy in the Indonesian Telecommunications Sector: The Role of Intervening Cash Holdings - Dea Yuliana; A Mukti Soma (International Journal Labs, 2026)
The telecommunications industry is capital-intensive, so the dividend policy must balance the interests of shareholders and internal financing. In this context, company cash plays a role in maintaining financial flexibility. This study analyzes the influence of free cash flow, leverage, profitability, and growth opportunities on dividend policy, either directly or through cash holdings as mediation. A quantitative approach with panel data regression was used on three telecommunications companies on the IDX (PT Telkom, PT Indosat, PT XL Axiata) for the 2013–2024 period. The appropriate estimation model is determined through Chow, Hausman, and Lagrange Multiplier tests. The results indicate that, simultaneously, free cash flow, leverage, profitability, and growth opportunities have an effect on cash holdings. However, partially, only profitability has a significant effect on cash holdings, while free cash flow, leverage, and growth opportunities do not show a significant influence. Furthermore, cash holdings do not have a significant effect on dividend policy, either partially or simultaneously. In addition, free cash flow, leverage, profitability, and growth opportunities also do not exhibit a significant impact on dividend policy, suggesting that dividend distribution decisions are not directly determined by these variables. Finally, cash holdings are not able to mediate the relationship between free cash flow, leverage, profitability, and growth opportunities and dividend policy. These findings indicate the need for other factors to support sustainable dividend policies in line with SDGs 8 and SDG 9.